Etiologies of chronic cough in adult patients: Is it hard to be diagnosed? - Abdul-Razaq, Mohammad Yahya; Sultan, Kassim M.; Muhammed, Shakir M. (AL-Kindy College Medical Journal, 2011)
Background: Chronic cough is often the key symptom not only of chronic pulmonary diseases but for other important extrapulmonary pathologies, in particular upper airway and gastrointestinal diseases. Objective: This study was designed to determine the etiology of chronic cough and the usefulness of the available diagnostic tests in reaching its causes. Methods: One hundred patients presenting with chronic cough at Baghdad Teaching Hospital Outpatient Clinic were enrolled in this study. The patients underwent a full clinical interview, physical examination with indicated diagnostic test(s) (such as chest x ray, bronchoscope, PFT, GIT study, sinus X ray or CT). Results: An etiology of chronic cough was determined in 93% of the patients. Post nasal drip is the leading cause of chronic cough reported in 31% of the patient, while asthma gastroesophageal reflux disease, and chronic bronchitis seen in (26, 20, and 6 % respectively). The diagnosis of chronic cough can be reached by comprehensive history, proper physical examination, and chest X ray findings in 66 % patients, further more sophisticated and invasive tests like: PFT, upper GIT study , expectorated sputum examination (AFB, Gram staining, cytology), fibrooptic bronchoscope, and full ENT evaluation including sinuses X ray or sinuses CT scanning, are need in the rest. Conclusion: The etiology of chronic cough can often be diagnosed safely with a simple initial evaluation (history, physical examination and chest X-ray). Postnasal drip, asthma and gastroesophageal reflux disease account for the etiology in more than three quarter of the patients.